Enteroscopy and radiology for the management of celiac disease complications: Time for a pragmatic roadmap. Issue 6 (June 2016) - Branchi, Federica; Locatelli, Martina; Tomba, Carolina; Conte, Dario; Ferretti, Francesca; Elli, Luca
Abstract: Celiac disease is the most common autoimmune enteropathy in Western countries, and is usually associated with a good response to the gluten free diet and an excellent prognosis. However, a minority of patients develop complications of the disease, such as refractory celiac disease, ulcerative jejunoileitis and neoplastic complications such as adenocarcinoma of the small bowel and enteropathy associated T cell lymphoma. Neoplastic complications described in association with celiac disease have a high mortality rate, due to their aggressive behavior and to the usual advanced stage at the time of diagnosis. In recent years, the detection of small bowel lesions has dramatically improved thank to the availability of highly performing radiologic and endoscopic techniques. The diagnostic delay of malignant complications in patients with celiac disease may be improved by establishing a pragmatic flowchart for the identification and follow up of "at risk" patients. We performed a comprehensive review of the articles published on this issue in order to promote a roadmap to be applied when facing with celiac patients with suspected small bowel complications.